Massenet and his letters Massenet en toutes lettres - Massenet, Anne 1939-; Massenet, Jules 1842-1912 (Pendragon Press, 2014)
Jules Massenet (1842-1912) is the author of twenty-five operas, oratorios, over two hundred eighty songs, and numerous instrumental works. When his descendant Anne Massenet was entrusted with the family archives, she discovered more than a thousand letters exchanged with his family, students, colleagues, friends, and even a few competitors! Anne Massenet's new biography, published in France in 2001, is now translated into English by Mary Dibbern. It reveals unknown aspects of Massenet's personality as documented by letters to his son-in-law Léon Alloend-Bessand who, even after his divorce from Juliette, the composer's only child, was his father-in-law's confident. Equally revealing are hundreds of other previously unpublished letters, mostly to his spouse Louise-Constance, nicknamed Ninon, whose long and frequent spa cures forced him to experience unbearable solitude. This is an intimate portrait of Massenet, seen through a unique collection of primary source documents
Title from publisher's bibliographic system (viewed on 01 Aug 2018)
Keywords: Massenet, Jules / 1842-1912; Massenet, Jules / 1842-1912 / Correspondence; Massenet, Jules -- 1842-1912; Composers / France / Biography; Quelle; Briefsammlung; Biografie